Barriers to the development of the circular economy in small and medium-sized enterprises in Slovakia - Michal Levický; Milan Fiľa; Milan Maroš; Marcela Korenková (Entrepreneurship and Sustainability Issues, 2022)
The circular economy is the successor to the current model of the linear economy. Its basic principle is the environmentally acceptable use of resources. At present, it can be understood as an intensively developing megatrend of the business environment. It can be assumed that the competitiveness of companies in the future will be highly dependent on how companies will be able to implement the principles of the circular economy. The article is focused on the analysis of the use of activities of the circular economy in the conditions of small and medium enterprises in Slovakia and on the willingness to finance these activities from the turnover of the company. Based on the conducted questionnaire survey, it was confirmed that smaller companies implement activities of the circular economy more slowly and their willingness to finance these activities is lower compared to larger companies. It can also be stated that if smaller companies carry out activities of the circular economy, these are mostly cost-free or low-cost activities. As the size of the company increases, so does the level of company involvement in the circular economy. The results achieved are similar in several areas to those of the Eurobarometer 2016. It may therefore appear that, despite the various activities of economic policy makers, there has been no shift in this area. However, it should be taken into account that our questionnaire survey was conducted during the Covid 19 virus pandemic, which has a significant impact on the business environment, business decision-making processes.